High-Coercivity Ferrimagnet Co₂FeO₂BO₃: XMCD Insights into Charge-Ordering and Cation Distribution - Mikhail S. Platunov (Inorganics)
The multi-sublattice ferrimagnet Co2FeO2BO3, a prominent example of lanthanide-free magnets, was the subject of element-selective studies using X-ray magnetic circular dichroism (XMCD) observations at the L- and K- X-ray absorption edges. Research findings indicate that the distinct magnetic characteristics of Co2FeO2BO3, namely its remarkable high coercivity (which surpasses 7 Tesla at low temperatures), originate from an atypical arrangement of magnetic ions in the crystal structure (sp.gr. Pbam). The antiferromagnetic nature of the Co2+-O-Fe3+ exchange interaction was confirmed by identifying the spin and orbital contributions to the total magnetization from Co (mL = 0.27 ± 0.1 μB/ion and meffS = 0.53 ± 0.1 μB/ion) and Fe (mL = 0.05 ± 0.1 μB/ion and meffS = 0.80 ± 0.1 μB/ion) ions through element-selective XMCD analysis. Additionally, the research explicitly revealed that the strong magnetic anisotropy is a result of the significant unquenched orbital magnetic moment of Co, a feature that is also present in the related compound Co3O2BO3. A complex magnetic structure in Co2FeO2BO3, with infinite Co²⁺O6 layers in the bc-plane and strong antiferromagnetic coupling through Fe3⁺ ions, is suggested by element-selective hysteresis data, which revealed that Co²⁺ ions contribute both antiferromagnetic and ferromagnetic components to the total magnetization. The findings underline the suitability of Co2FeO2BO3 for applications in extreme environments, such as low temperatures and high magnetic fields, where its unique magnetic topology and anisotropy can be harnessed for advanced technologies, including materials for space exploration and quantum devices. This XMCD study opens the door to the production of novel high-coercivity, lanthanide-free magnetic materials by showing that targeted substitution at specific crystallographic sites can significantly enhance the magnetic properties of such materials.